Endometrial hyperplasia and endometrial polyps: clinical and anamnestic characteristics of women - E. N. Kravchenko; E. V. Lautenschleger (Фундаментальная и клиническая медицина)
Aim. To study the clinical and anamnestic characteristics of patients with endometrial hyperplasia (EH) and endometrial polyps (PE).Material and Methods. a retrospective study was conducted, which included 267 sick women of reproductive and perimenopausal age who sought gynecological care at «Euromed» in 2022-23, who, before receiving the examination results, were diagnosed with N92 - heavy, frequent and irregular menstruation. Depending on the results of the pathomorphological examination, the patients were divided into 3 groups: group A included 89 patients with GE; group B – 99 women with PE; Group B (control) included 79 patients in whom endometrial pathology was excluded.Results. Among all women who came to the clinic with heavy menstrual bleeding, 33.3% had GE, 37.1% had PE, 29.6% had BUN-O ovulatory dysfunction. GE without atypia was detected in 72 (80.9%) cases of group A, GE with atypia – in 7 (19.1%), in group B PE was diagnosed in 91 (91.9%) cases, PE with atypia – in 28 (8.1%).In group B, in 22 (27.8%) cases, the endometrium was identified in the proliferation phase, in 57 (72.2%) cases, the endometrium was identified in the phase of incomplete secretion.Conclusion. Women with GE are characterized by early menarche, absence of pregnancies and childbirth during life associated with the woman’s choice, contraception, endocrine diseases, obesity, polycystic ovary syndrome, ovarian tumors, heavy bleeding with clots during menstruation, menstruation for more than 8 days, chronic iron deficiency anemia. Women with endometrial polyps are characterized by arterial hypertension, uterine fibroids, adenomyosis, infertility, dysmenorrhea, chronic endometritis, a history of cervicitis and vaginitis; clinical manifestations include intermenstrual bleeding.